Annual Plan, 1994-95 Orissa Vol. I - Planning Commission (Planning Commission, 1994)
The policy of reservation in jobs in respect of the socially backward unemployed youth has been strictly implemented by the State Government. Special employment exchanges for S.C. and S.T., Physically handicapped persons and Ex-servicemen have been set up. State Government have also provided 30 per cent reservation for women candidates.
Government of Orissa